Sociological analysis and interpretation of factors and barriers to strengthening (consolidation) the foundation of the family (From the perspective of experts and clients refer to the family court of zanjan) - Abbasi, Roghayeh; Pourjabali, Robabeh; Zolghadr, Khadijeh (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The purpose of the current research was to analyze and sociologically interpret the factors and obstacles of strengthening the family foundation from the perspective of experts and those referring to the family court of Zanjan city. Methods: The current research was a survey that was conducted through a questionnaire with the Delphi technique and in-depth interviews with semi-structured sampling, and a survey method with simple random probability sampling, as well as by collecting library and field information. Results: The results indicate that: According to experts, emotional factors, belief factors, cultural factors, economic factors, social factors, as well as belief barriers, emotional barriers, social barriers, economic barriers and cultural barriers in strengthening the foundation, respectively. Conclusion: Families are effective. There is also a direct and significant relationship between gender, how to choose a spouse, couple satisfaction, joint efforts in family affairs, solidarity of family members, the level of trust between family members and the level of family life skills and strengthening the family foundation.